2014
DOI: 10.1007/s11141-014-9520-y
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of Operation of a Relativistic Backward-Wave Oscillator Driven by an External Electromagnetic Signal

Abstract: 621.385.6 We study operation of a relativistic backward-wave oscillator driven by an external electromagnetic signal. Such operation regimes as hard excitation of self-oscillations and amplification of the external signal are implemented experimentally. The conditions for possible synchronization of the relativistic backward-wave oscillator by an external signal is discussed. The possibility of accelerating the onset of oscillations by the action of an external signal is confirmed experimentally. The condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The "meeting" of a seed pulse peak and the current front should be provided near the SWS input (ii), and at the moment of time when the electron energy at the current front attains the band of beam-wave Cherenkov synchronism (iii). Under such conditions for the power ratio of ~4 In agreement with results [20], [21], where the influence of an external signal on operation of a long pulse relativistic BWO was studied, we also observed that in the presence of a seed pulse, the pulse 1 SR formation occurs somewhat earlier than in the case of the free-running regime [see delayed dashed envelope of the pulse 2 SR in Fig. 7 (b)].…”
Section: Initiation Of Sr Pulse Emission By An External Em Pulsesupporting
confidence: 89%
“…The "meeting" of a seed pulse peak and the current front should be provided near the SWS input (ii), and at the moment of time when the electron energy at the current front attains the band of beam-wave Cherenkov synchronism (iii). Under such conditions for the power ratio of ~4 In agreement with results [20], [21], where the influence of an external signal on operation of a long pulse relativistic BWO was studied, we also observed that in the presence of a seed pulse, the pulse 1 SR formation occurs somewhat earlier than in the case of the free-running regime [see delayed dashed envelope of the pulse 2 SR in Fig. 7 (b)].…”
Section: Initiation Of Sr Pulse Emission By An External Em Pulsesupporting
confidence: 89%
“…The problem of a high-power multimode electron oscillator injection locking by an external driving signal has attracted a considerable interest. The injection locking allows for controlling the radiation frequency and phase of high-power microwave sources, [1][2][3][4][5] as well as reducing transient times. 5,6 Also, a low-power external driving of a high-power oscillator may result in the fast frequency step tuning owing to the mode switching effect.…”
mentioning
confidence: 99%
“…The injection locking allows for controlling the radiation frequency and phase of high-power microwave sources, [1][2][3][4][5] as well as reducing transient times. 5,6 Also, a low-power external driving of a high-power oscillator may result in the fast frequency step tuning owing to the mode switching effect. [7][8][9] Nevertheless, the fundamentals of the mode switching are still poorly understood.…”
mentioning
confidence: 99%